Inter-annual prey fluctuation of Odocoileus virginianus in Maya group hunting (batida) in the Yucatan Peninsula - Burgos-Solís, Yahir; Montiel, Salvador; Castillo-Burguete, Teresa; Ibarra-Cerdeña, Carlos N.; Porter-Bolland, Luciana (Ecosistemas y Recursos Agropecuarios, 2023)
In Neotropical environments, we know little about the abundance of wild vertebrates traditionally hunted. Based on subsistencehunting records (2005-2019) as well as ethnographic information from Maya peasant-hunters, we assessed the inter-annual capture rate of white-tailed deer (Odocoileus virginianus) in a rural community in the northwest of the Yucatan Peninsula. We found that the number of prey decreased over the years, showing a declining capture rate (prey/trip) that decreased by as much as 50% from the first (2005-2006) to the third period (2010-2011) of records. The majority of peasant-hunters interviewed (74%; N = 31) perceived this reduction in deer to have taken place mainly over the past 10 years as consequence of hunting (71%). The agreement between the hunting trend and peasants’ perceptions regarding the abundance of white-tailed deersuggests that this species may be at risk in future scenarios of use in northwest of contemporary Mayab.
Keywords: Subsistence hunting; Maya batida; Los Petenes Biosphere Reserve